Negative Application Conditions for Reconfigurable Place/Transition Systems - Rein, Alexander; Prange, Ulrike; Lambers, Leen; Hoffmann, Kathrin; Padberg, Julia (Electronic Communications of the EASST, 2008)
This paper introduces negative application conditions for reconfigurable place/transition nets. These are Petri nets together with a set of rules that allow changing the net and its marking dynamically. Negative application conditions are a control structure that prohibits the application of a rule if certain structures are already existent. We motivate the use of negative application conditions in a short example. Subsequently the underlying theory is sketched and the results – concerning parallelism, concurrency and confluence – are presented. Then we resume the example and explicitly discuss the main results and their usefulness within the example.